The Environmental Impact of The Plastic Products Industry in Jiaozuo City and the Species Subject to Priority Control - Yue, Junhui; Feng, Shaoxin; Sun, Linghe (International Journal of Natural Resources and Environmental Studies, 2025)
As an important emission source of volatile organic compounds (VOCs), the plastic products industry has relatively few studies conducted on it. Therefore, this paper selects seven plastic products enterprises in Jiaozuo City for monitoring and analysis. By calculating the ozone formation potential and secondary organic aerosol formation potential of the plastic products industry, the environmental impact of this industry is understood. Through the calculation using the entropy method, the species subject to priority control in this industry are determined. The results show that in the plastic products industry of Jiaozuo City, the daily-use plastic products manufacturing industry has the highest VOCs concentration, which is 20.18 mg/m³, followed by the plastic pipe manufacturing industry (3.96 mg/m³), the synthetic leather made of plastics manufacturing industry (1.93 mg/m³), and the plastic packaging boxes and containers manufacturing industry (0.27 mg/m³). Among them, OVOCs are the main components of the plastic products industry, and the main contributing substances include ethyl acetate, n-butanal, 2-butanone, etc. The main contributing components of the plastic products industry to ozone formation and secondary organic aerosol formation are OVOCs and aromatic hydrocarbons respectively, and the main contributing substances are ethyl acetate, n-butanal, propionaldehyde, ethylbenzene, and toluene respectively.